Perancangan Desain UI/UX Aplikasi Jual Beli Hasil Pertanian Pasar Tani Ogan Ilir Berbasis Mobile Menggunakan Metode Design Thinking - Dendi Sanjaya; Taqrim Ibadi (LPPM STIKOM Tunas Bangsa, 2023)
Agriculture is a major source of income and source of livelihood for the people of Indonesia. Ogan Ilir Regency has an area of 2,666.09 km2, out of a total population of 416,549 people, the main occupation status of the residents of Ogan Ilir is 40,505 people self-employed, 45,899 people as temporary workers, 6,805 people as permanent workers, 42,670 people as family/unpaid workers, Of the four main types of work, almost all of them work as farmers, while the remaining 71,055 employees/employees and 11,821 freelancers. The vast area of Ogan Ilir district can be a good potential to improve the economy of farmers. But on the other hand, many farmers and consumers have suffered losses due to problems arising from the long system of selling agricultural products in the Ogan Ilir district. This problem must be resolved immediately, one of the efforts that can be done is to design the UI / UX application for buying and selling agricultural products based on mobile-based Ogan Ilir Farmers Market using the Design Thinking method. The purpose of this study was to design a UI/UX design for an application for buying and selling agricultural products based on the Ogan Ilir Farmer's Market. This research was conducted in the district of Ogan Ilir to be precise at the Office of the Agricultural Extension Center (BPP) Kec.Tanjung Raja using quantitative research methods. The results of this study are the prototype of the Ogan Ilir Farmers Market application and the results of usability testing which contains data on the use of the designed UI/UX design. The conclusion of this study is the result of designing the UI/UX design of a mobile-based buying and selling application from the Ogan Ilir Farmers Market which has been designed to be suitable for use as an initial design for the future development of the Ogan Ilir Farmers Market application. It is said to be feasible because the click error rate is below 50%, which is only 7%, besides that the number of respondents who completed the mission according to the path was also more than 50%, which was 97.8% and was also based on the opinions of 397 respondents who stated that the prototype design had been proper to use